Acute Toxicity Test of Jernang Resin Extract (Daemonorops Draco Willd.) on Male White Rats Sprague Dawley Strain - Fidia Yunita; Lavlinesia; Mursyid (Indonesian Food Science and Technology Journal, 2019)
Keywords— Jernang resin extract; white rats; acute toxicity